2017
DOI: 10.3390/v9120391
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Cowpox Virus (CPXV) Infections of Bank Voles: Exceptional Clinical Resistance and Variable Reservoir Competence

Abstract: Cowpox virus (CPXV) is a zoonotic virus and endemic in wild rodent populations in Eurasia. Serological surveys in Europe have reported high prevalence in different vole and mouse species. Here, we report on experimental CPXV infections of bank voles (Myodes glareolus) from different evolutionary lineages with a spectrum of CPXV strains. All bank voles, independently of lineage, sex and age, were resistant to clinical signs following CPXV inoculation, and no virus shedding was detected in nasal or buccal swabs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The outcome of all these animal experiments further substantiates the recent hypothesis of reservoir species-specific phylogenetic lineages within the CPXV classification [31]. As depicted in Table 4, different CPXV strains display clearly different behavior in the different corresponding presumed reservoir animals and the Wistar rat animal model.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The outcome of all these animal experiments further substantiates the recent hypothesis of reservoir species-specific phylogenetic lineages within the CPXV classification [31]. As depicted in Table 4, different CPXV strains display clearly different behavior in the different corresponding presumed reservoir animals and the Wistar rat animal model.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, growth kinetics of CPXV GerMygEK 938/17 on Vero76 cells in comparison to those of other CPXV strains like Brighton Red, RatPox09, or the very closely related CPXV strain Ger2010MKY allowed no proposition concerning the in vivo virulence. While all four tested CPXV strains showed a very similar outcome in the replication kinetics on Vero76 cells, the results of the animal experiments differed markedly [31]. Along with a previous study, we concluded that in vitro assays could not predict in vivo properties or virulence differences [39].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations